Amyloplast-Localized SUBSTANDARD STARCH GRAIN4 Protein Influences the Size of Starch Grains in Rice Endosperm . Issue 2 (13th December 2013) - Matsushima, Ryo; Maekawa, Masahiko; Kusano, Miyako; Kondo, Hideki; Fujita, Naoko; Kawagoe, Yasushi; Sakamoto, Wataru
Abstract : A novel amyloplast-localized protein, SSG4, influences the size of starch grains in rice endosperm . Abstract: Starch is a biologically and commercially important polymer of glucose and is synthesized to form starch grains (SG s) inside amyloplasts. Cereal endosperm accumulates starch to levels that are more than 90% of the total weight, and most of the intracellular space is occupied by SG s. The size of SG s differs depending on the plant species and is one of the most important factors for industrial applications of starch. However, the molecular machinery that regulates the size of SG s is unknown. In this study, we report a novel rice ( Oryza sativa ) mutant called substandard starch grain4 ( ssg4 ) that develops enlarged SG s in the endosperm. Enlargement of SG s in ssg4 was also observed in other starch-accumulating tissues such as pollen grains, root caps, and young pericarps. The SSG4 gene was identified by map-based cloning. SSG4 encodes a protein that contains 2, 135 amino acid residues and an amino-terminal amyloplast-targeted sequence. SSG4 contains a domain of unknown function490 that is conserved from bacteria to higher plants. Domain of unknown function490-containing proteins with lengths greater than 2, 000 amino acid residues are predominant in photosynthetic organisms such as cyanobacteria and higher plants but are minor in proteobacteria. The results of this study suggest that SSG4 is a novel protein that influences the size of SG s. SSG4 will be a useful molecular tool for future starch breeding and biotechnology.